Respuesta :

Answer:

y = 2(x-3)^2 - 2

Step-by-step explanation:

y = 2x^2 - 12x + 16

y = 2(x^2 - 6x + 8)

y = 2(x^2 - 6x +8 +1 -1) you "complete the square" by bringing the last term (8) up to "half of the middle co-efficient squared". Middle co-efficient is -6, half is -3, squared is 9. To get from 8 to 9 you must add 1 (+1), but if you add 1 you must subtract 1 (-1) so that you don't change the overall value of inside the bracket


y = 2(x^2 - 6x +9) - 2 (bring the -1 outside of the brackets)

y = 2(x-3)^2 - 2